Viability of The Lactobacillus casei Probiotic in Yoghurt from Goat Milk during Frozen Storage - Cahyanti, Antonia Nani (Jurnal Teknologi Pertanian, 2011)
This research was conducted to study the viability of the probiotic L. casei in yoghurt from goat’s milk during frozen storage. Yoghurts were made with L. casei as a probiotic starter, stored in freezer for 0, 2, 4, and 6 days and also evaluated for pH, acidity, and probiotic count. The result showed that probiotic growth was decreased just on the 2nd day of storage significantly, and it was marked with the decreasing of acidity, probiotic count, and the increasing of pH. The probiotic seemed to be adaptive with the freezing condition after the 2 nd day of storage until the 6 day of storage. It was marked with the increasing of probiotic count, acidity, and the decreasing of pH. The probiotic count at the end of frozen storage were 7.96 log CFU/mL, wich fullfilled the Codex Allimentarius requirement for fermented milk consumption.